Congo - Kennedy, Kathleen; Mercer, Sam; Marshall, Frank (USA : Paramount Pictures, 2002)
They've eluded heat-seeking missiles, gone eyeball-to-eyeball with enraged 5,000 pound hippos, hacked through a jungle curtain. Still, the expedition continues. Amy, a gorilla who was part of a university learning experiment, is a last returning home. A professor (Dylan Walsh), electronics expert (Laura Linney), guide (Ernie Hudson), explorer (Tim Curry) and others follow the scampering ape. They know she will lead them to the place that's more than her home-it's the site of the fabled Lost City of Zinj and its diamond mines. But what they don't know can be fatal. Once they enter Zinj, they'll be the endangered species!
Edited by Anne V. Coates ; music by Jerry Goldsmith ; director of photography, Allen Daviau
Cast: Dylan Walsh, Laura Linney, Ernie Hudson, Tim Curry
Keywords: Adventure film